Pengabdian Kepada Masyarakat Dengan Tema Strategi Komunikasi Berbasis E-Commerce Dalam Penjualan Bebek Ungkep Beku Di Desa Pakuncen Kecamatan Bojonegara - Fithrotul Kamilah; Agustina Dwiyanti; Ira Damayanti; Eli Apud Saepudin (WINDRADI: Jurnal Pengabdian Masyarakat, 2024)
Communication is one of the main keys in building and developing MSMEs (Micro, Small and Medium Enterprises) Determining Target Audience Building Brand Identity Determining Communication Channels Creating Engaging Content Building Interaction and Community Utilizing Technology Measuring and Evaluating Results E-commerce, or electronic commerce, has grown rapidly in recent years and offers various opportunities for businesses and consumers. However, along with these opportunities, e-commerce also faces some challenges that need to be overcome. E-Commerce Opportunities Wide Market Reach, Lower Operating Costs, Ease and Convenience, Greater Product Variety, Efficiency and Automation, Personalization. Community Service is currently located in Pakuncen Village, Bojonegara District with four lecturers from Bina Bangsa University, the purpose of this service is to provide education to the people of Pakuncen Village, Bojonegara District